Emerging Trends of Nanofibrous Piezoelectric and Triboelectric Applications Mechanisms, Electroactive Materials, and Designed Architectures - Zhi, Chuanwei (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.